Environmental Criminal Law as a Tool for Ecological Protection: Interpreting the Constitution in the Context of Environmental Crimes - Ramada, Diandra Preludio; Kamal, Ubaidillah; Utari, Indah Sri (Semarang State University Undergraduate Law and Society Review, 2025)
This article comprehensively analyzes the Indonesian Constitution as a crucial foundation and solid bulwark for strengthening Environmental Criminal Law. Given the alarming global ecological crisis, characterized by massive deforestation, uncontrolled pollution, biodiversity loss, and excessive resource exploitation, reforming the criminal law framework to be adaptive, responsive, and progressive is urgent. This research firmly argues that the Constitution isn't just a general, declarative legal umbrella; it intrinsically embodies fundamental constitutional values and principles. These include every citizen's right to a good and healthy environment and the state's obligation to protect it, which must be actively interpreted, internalized, and expanded into all norms and practices of Environmental Criminal Law enforcement. Using a normative-juridical approach focused on analyzing legal texts, doctrines, and court decisions, this article systematically examines how in-depth constitutional interpretation and creative elaboration of principles can catalyze stronger, more comprehensive, and ecologically just environmental criminal regulations. The discussion identifies and critically analyzes structural and substantive weaknesses in current environmental criminal law enforcement, such as evidentiary challenges, weak sanctions, and limited scope of legal subjects. Furthermore, this article explores the Constitution's potential to legitimize overcoming these obstacles. This includes strengthening criminal sanctions for proportional deterrence, expanding the definition of environmental crimes to encompass new and complex ecological offenses, and enhancing more effective corporate accountability mechanisms. Ultimately, this article affirms that reforming and developing Environmental Criminal Law, firmly rooted in constitutional values and principles, is an absolute prerequisite for building a holistic and sustainable environmental protection system. This step is essential in preventing further ecological degradation, restoring the balance of nature, and effectively guaranteeing environmental rights for current and future generations.